Fusion of sensor information to measure the total energy of an aircraft and provide information about flight performance and local microclimate - Johnson, Bruce (Department of Electrical Engineering, 2023)
The application of using Unmanned Aerial Vehicles (UAVs) to locate thermal updraft currents is a relatively new topic. It was first proposed in 1998 by John Wharington, and, subsequently, several researchers have developed algorithms to search and exploit thermals. However, few people have physically implemented a system and performed field testing. The aim of this project was to develop a low cost system to be carried on a glider to detect thermals effectively. A system was developed from the ground up and consisted of custom hardware and software that was developed specifically for aircraft. Data fusion was performed to estimate the attitude of the aircraft; this was done using a direction cosine (DCM) based method. Altitude and airspeed data were fused by estimating potential and kinetic energy respectively; thus determining the aircraft's total energy. This data was then interpreted to locate thermal activity. The system comprised an Inertial Measurement Unit (IMU), airspeed sensor, barometric altitude sensor, Global Positioning System (GPS), temperature sensor, SD card and a realtime telemetry link. These features allowed the system to determine aircraft position, height, airspeed and air temperature in realtime. A custom-designed radio controlled (RC) glider was constructed from composite materials in addition to a second 3.6 m production glider that was used during flight testing. Sensor calibration was done using a wind tunnel with custom designed apparatus that allowed a complete wing with its pitot tube to be tested in one operation. Flight testing was conducted in the field at several different locations over the course of six months. A total of 25 recorded flights were made during this period. Both thermal soaring and ridge soaring were performed to test the system under varying weather conditions. A telemetry link was developed to transfer data in realtime from the aircraft to a custom ground station. The recorded results were post-processed using Matlab and showed that the system was able to detect thermal updrafts. The sensors used in the system were shown to provide acceptable performance once some calibration had been performed. Sensor noise proved to be problematic, and time was spent alleviating its effects. Results showed that the system was able to measure airspeed to within ± 1 km/h. The standard deviation of the altitude estimate was determined to be 0.94 m. This was deemed to be satisfactory. The system was highly reliable and no faults occurred during operation. In conclusion, the project showed that inexpensive sensors and low power microcontrollers could be used very effectively for the application of detecting thermals.